CURRENT RATIO, QUICK RATIO, DEBT TO ASET RASIO AND DEBT TO EQUITY RATIO TO RETUR ON EQUITY IN FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Muis Fauzi Rambe; Nur Anisah (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to analyze and determine the effect of Current Ratio, Quick Ratio, Debt To Asset Ratio and Debt to Total Equity Ratio on Return On Equity in food and beverage companies listed on the Indonesia Stock Exchange. The population used in this study amounted to 26 companies. Data collection techniques in this study using documentation techniques. The data analysis technique in this study uses the Classical Assumption Test, Multiple Linear Regression, t-test and F-test, and the Coefficient of Determination. Data management in this study using the SPSS 23 Software program. The results showed that the Current ratio had no positive but significant effect on Return on Equity.in food and beverage companies listed on the IDX for the 2016-2020 period. The quick ratio does not have a positive but significant effect on Return on Equity in food and beverage companies listed on the IDX for the 2016-2020 period. The Debt To Asset Ratio has no positive but significant effect on Return on Equity in food and beverage companies listed on the IDX 2016-2020. The Debt To Equity Ratio has no positive but significant effect on Return on Equity in food and beverage companies listed on the IDX for the 2016-2020 period. Current Ratio, Quick Ratio, Debt to Asset Ratio and Debt to Equity Ratio together do not have a positive but significant effect on the Return on Equity of food and beverage companies listed on the IDX for the 2016-2020 period.Keywords: Current Ratio, Quick Ratio, Debt to Asset Ratio and Debt to Equity Ratio and Return on Equity